The reversal of fortune, extractive institutions and the historical roots of racism - Matthew Bonick; Antonio Farfán-Vallespín (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2018)
We show that differences in present levels of racism within a sample of former European colonies can be traced back to historical institutions. Our identification strategy relies on the reversal of fortune, a historical shock capturing the exogenous establishment of different institutions during the onset of European colonization. Using both OLS and multilevel analysis, we find extractive historical institutions to be a strong predictor of higher levels of racism independent of present and other explanatory factors at the individual and country levels. We argue and provide evidence this relationship is causal and operates through persistent internal norms, beliefs and values, resilient to changes in institutional and economic circumstances.
Keywords: 330